How users' knowledge of advertisements influences their viewing and selection behavior in search engines - Schultheiß, Sebastian; Lewandowski, Dirk (Journal of the American Society for Information Science and Technology, 2021)
According to recent studies, search engine users have little knowledge of Google's business model. In addition, users cannot sufficiently distinguish organic results from advertisements, resulting in result selections under false assumptions. Following on from that, this study examines how users' understanding of search‐based advertising influences their viewing and selection behavior on desktop computer and smartphone. To investigate this, we used a mixed methods approach (n = 100) consisting of a pre‐study interview, an eye‐tracking experiment, and a post‐study questionnaire. We show that participants with a low level of knowledge on search advertising are more likely to click on ads than subjects with a high level of knowledge. Moreover, subjects with little knowledge show less willingness to scroll down to organic results. Regarding the device, there are significant differences in viewing behavior. These can be attributed to the influence of the direct visibility of search results on both devices tested: Ads that were ranked on top received significantly more visual attention on the small screen than the top ranked ads on the large screen. The results call for a clearer labeling of advertisements and for the promotion of users' information literacy. Future studies should investigate the motivations of searchers when clicking on ads.